Mapping Work in Early Twentieth-Century Montreal: A Rabbi, a Neighbourhood, and a Community - Poutanen, Mary; Gilliland, Jason (Urban History Review / Revue d'histoire urbaine, 2017)
Rabbi Simon Glazer’s 1909 daily journal provides a window onto his role as an orthodox rabbi of a largely Yiddish-speaking immigrant community, his interactions with Jewish newcomers, the range of tasks he performed to augment the inadequate stipends he received from a consortium of five city synagogues where he was chief rabbi, and the ways in which Jewish newcomers sought to become economically independent. Using a multidisciplinary methodology, including Historical Geographic Information Systems (HGIS), Glazer’s journal offers a new lens through which to view and map the social geography of this community. Our study contributes to a growing body of literature on immigrant settlement, which has shown that such clustering encouraged economic independence and social mobility.  Characterized by a high degree of diversity in ethnicity and commerce, the St. Lawrence Boulevard corridor was an ideal location for Jewish newcomers to set down roots. We argue that the community served as a springboard for social mobility and that Simon Glazer played an important role at a critical moment in its early development.  It was on its way to becoming one of Canada’s most significant Jewish communities.  Over the eleven years that he worked in Montreal (1907–18), Glazer carved out a vital place for himself in the city’s Jewish immigrant community and honed skills that would serve him well when he returned to the United States.